(untitled) (Indian Journal of Public Health Research & Development, 2022)
Heart failure with preserved ejection fraction(HFpEF) is an entity showing an upward trend. The affected population is rising on account of rise in the geriatric population as well as expanding incidence of comorbidities,thus underlining the necessity of greater therapeutic avenues. The underlying disease mechanisms are complicated. Irrespective of EF, HFpEF negatively influences quality of life and hard clinical endpoints. Greater research into HFpEF phenotypes, criteria for definition and improvement in prognosis is the need of the hour.